Intentional vomiting as a rare cause of hypercalcemia and consequent acute renal failure: a case report - Santini, Mihovil; Sorić, Ana; Mioč, Pavao; Car, Siniša; Đula, Kristijan; Zeljkovic, Ivan (Frontiers in Medicine, 2024)
Two most common causes of elevated serum calcium levels, which together account for nearly 90% of all cases, are primary hyperparathyroidism and malignancy. Thus, it is necessary to consider other disorders in the diagnostic evaluation of patients with hypercalcemia. We report the case of a 40-year-old female patient with an intellectual disability who was admitted to the Emergency Department with severe symptomatic hypercalcemia and acute renal failure, caused by recurrent intentional vomiting. The aim of this report is to help clinicians make an accurate diagnosis by considering recurrent vomiting habits as a potential cause of hypercalcemia and acute renal failure. Our case provides a comprehensive diagnostic work-up and multidisciplinary treatment strategies for patients with symptomatic hypercalcemia.